2022
DOI: 10.1021/acs.bioconjchem.2c00355
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Fluorescent Labeling of the Cysteine-Rich Toxin, DkTx, for TRPV1 Ion Channel Imaging and Membrane Binding Studies

Abstract: Peptide toxins secreted by venomous animals bind to mammalian ion channel proteins and modulate their function. The high specificity of these toxins for their target ion channels enables them to serve as powerful tools for ion channel biology. Toxins labeled with fluorescent dyes are employed for the cellular imaging of channels and also for studying toxin-channel and toxin-membrane interactions. Several of these toxins are cysteine-rich, rendering the production of properly folded fluorescently labeled toxins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…We envisioned that the presence of a large number of cysteines in our proposed tetra-knots (24 in each molecule) would render their production challenging due to the likelihood of these cysteines forming non-native mixed disulfides during folding. This apprehension was supported by our recent work on labeling DkTx with a fluorophore that revealed that introducing a non-native cysteine into DkTx results in the formation of misfolded toxin species ( 26 ). Therefore, instead of attempting to produce the tetra-knots by employing our standard protocol for producing DkTx that entails expressing the full-length linear protein in E. coli followed by subjecting it to redox folding conditions, we employed a step-wise approach involving the production of properly folded precursor double-knots followed by their enzymatic ligation to form the desired tetra-knots.…”
Section: Resultsmentioning
confidence: 85%
“…We envisioned that the presence of a large number of cysteines in our proposed tetra-knots (24 in each molecule) would render their production challenging due to the likelihood of these cysteines forming non-native mixed disulfides during folding. This apprehension was supported by our recent work on labeling DkTx with a fluorophore that revealed that introducing a non-native cysteine into DkTx results in the formation of misfolded toxin species ( 26 ). Therefore, instead of attempting to produce the tetra-knots by employing our standard protocol for producing DkTx that entails expressing the full-length linear protein in E. coli followed by subjecting it to redox folding conditions, we employed a step-wise approach involving the production of properly folded precursor double-knots followed by their enzymatic ligation to form the desired tetra-knots.…”
Section: Resultsmentioning
confidence: 85%
“…30,31 In addition, a labeled toxin for imaging the rat TRPV1 ion channel could be obtained by connecting an agonist double-knot toxin (DkTx) with fluorescent molecules. 32 Together, these results indicate that peptide toxins with high activity and selectivity for specific subtypes of ion channels can serve as ideal pharmacological tools for visualizing and imaging ion channels when linked to various fluorescent molecules.…”
Section: Introductionmentioning
confidence: 85%
“…For example, the fluorescent molecule 5-carboxytetramethylrhodamine succinimidyl ester (5-TAMRA-SE) could react with the N-terminus of α-CTx LtIA targeting α3β2 nAChR to obtain a novel fluorescent analog of LtIA . Other α-CTxs, such as MII and TxID (targeting α3β2 and α3β4 nAChRs, respectively), could also connect with different fluorescent molecules, providing pharmacological tools for exploring the functional neuroanatomy of various subtypes of nAChRs. ,, Scorpion toxins targeting voltage-gated potassium ion (K V ) channels could also be linked to different fluorescent molecules, such as HsTX1­[R14A], OSK1, and AgTx2, serving as pharmacological tools for studying K V channels. , In addition, a labeled toxin for imaging the rat TRPV1 ion channel could be obtained by connecting an agonist double-knot toxin (DkTx) with fluorescent molecules . Together, these results indicate that peptide toxins with high activity and selectivity for specific subtypes of ion channels can serve as ideal pharmacological tools for visualizing and imaging ion channels when linked to various fluorescent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…To visualise the expression and distribution of TRPV1 channels, double-knot-toxin (DkTx) from tarantula Ornithoctonus huwena venom [ 151 ] conjugated with fluorescein via sortase at the C-terminus was applied to Xenopus leaves oocytes transfected with rat TRPV1 channels [ 152 ] (Table 5 ; Fig. 2 ).…”
Section: Optical Probes Targeting Trp Channelsmentioning
confidence: 99%
“…Because DkTx contains a large number of cysteine residues, cysteine-mediated bioconjugation caused a high level of misfolding of the toxin. Nevertheless, the authors report that their approach enabled successful and selective labelling of rat TRPV1 in the oocyte model [ 152 ].…”
Section: Optical Probes Targeting Trp Channelsmentioning
confidence: 99%